2009
DOI: 10.3390/s91210309
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurements and Guidelines for the Application of Wireless Sensor Networks to the Environment and Security

Abstract: Frequently, Wireless Sensor Networks (WSN) are designed focusing on applications and omitting transmission problems in these wireless networks. In this paper, we present a measurement campaign that has been carried out using one of the most commonly used WSN platforms, the micaZ from Crossbow©. Based on these measurements, some guidelines to deploy a robust and reliable WSN are provided. The results are focused on security and environmental applications but can also be extrapolated to other scenarios. A main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The SensorScope [5] project has shown that many factors such as harsh weather conditions can greatly influence the performance of WSNs regarding the reliability of delivery and quality of measurements. Indoor experiments with WSNs [6] suggest that the deployment location of sensor nodes such as height influence radio waves. In outdoor sensor network research it has been shown that the RSSI changes greatly [7].…”
Section: Discussionmentioning
confidence: 99%
“…The SensorScope [5] project has shown that many factors such as harsh weather conditions can greatly influence the performance of WSNs regarding the reliability of delivery and quality of measurements. Indoor experiments with WSNs [6] suggest that the deployment location of sensor nodes such as height influence radio waves. In outdoor sensor network research it has been shown that the RSSI changes greatly [7].…”
Section: Discussionmentioning
confidence: 99%
“…). Several authors [17,18] have identified a series of requirements for healthcare applications that are based on wireless technologies, including: Reliability: the transmission of precise data, which involves preventing the duplication of information, by implementing an efficient Quality of Service (QoS) which insures a high Packet Delivery Ratio (PDR) and reduces the Packet Loss Rate (PLR).Energetic efficiency: the development or use of an energy-saving algorithm or technology to reduce the consumption of energy in devices, because this helps extend the life span of the network.Data routing: the use of an efficient communication protocol that provides scalability, failure tolerance and best possible route selection, among others.Node mobility: the ability of free moving wireless nodes to move within an indoor area, always maintaining optimum connectivity.Security: the use of efficient security mechanisms to protect the data and privacy of highly sensible patient information, including its robbery or corruption.…”
Section: Related Workmentioning
confidence: 99%
“…). Several authors [ 17 , 18 ] have identified a series of requirements for healthcare applications that are based on wireless technologies, including: Reliability: the transmission of precise data, which involves preventing the duplication of information, by implementing an efficient Quality of Service (QoS) which insures a high Packet Delivery Ratio (PDR) and reduces the Packet Loss Rate (PLR). Energetic efficiency: the development or use of an energy-saving algorithm or technology to reduce the consumption of energy in devices, because this helps extend the life span of the network.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A wireless sensor network (WSN) consists of a large number of spatially-distributed, low-cost sensors to monitor and gather information about various physical phenomena within the sensing field. Wireless sensor networks are an active research area in computer science and telecommunication and have been widely used in a variety of applications nowadays, such as precision agriculture, environment sensing, military surveillance, and so on [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%